The Simple Model of Newton's II Law and Its Applications (International Journal of Innovative Research in Computer Science & Technology, 2023)
The research aims to determine The  Simple model for Newton’s II Law and its application.  The sample of this study is 20 sample variation. Data  analysis technique used is by regression analysis. From the  results of the analysis it was found that Freghitung=4,28 and Freg-table =4,13 (Freg-count >Freg-table), so the  conclusion of this study is that there is a very large the  simple model of Newton’s II law and its application.
Keywords: Simple Model; Newton’s II Law; Newton’s II Law Application